Prevalence of Microalbuminuria in Hypertensive Patients - More, Dr. Nilesh Gangadhar; Dumade, Dr. Priyank; Agrahari, Dr. Navneet; Gaikwad, Dr. Madhukar (International Journal of Innovative Research in Medical Science, 2018)
A total of 657 uncontrolled hypertensive patients (BP > 140/90 mm Hg in non-diabetics and BP >130/85 mm Hg in diabetic patients) were studied and followed for 12 months. Out of which 374 (56.93%) were male and 283 (43.07%) were female. Retinopathy was observed in 91 (13.85%) cases and Left ventricular hypertrophy was seen in 91 (13.85%) patients. Out of 374 male patients 198 (52.94%) were smokers while 176 (47.06%) were non-smokers. Hypertension is an established risk factor for cardiovascular as well as renal disease. Prevalence of microalbuminuria in hypertensive patients suggests that screening for microalbuminuria is essential for intervention and prevention of further complications like end stage renal disease and cardiovascular disease. It is much more essential to screen for early nephropathy by testing microalbuminuria in hypertensive patients prevent or halt the earliest stages of damage by vigorous control of hypertension. Further studies in large scale population are required to further verification of microalbuminuria as a screening tool to prevent progression of cardiovascular and renal disease.